On the relative effect of spawning asynchrony, sperm quantity, and sperm quality on paternity under sperm competition in an external fertilizer - Egeland, Torvald B.; Rudolfsen, Geir; Nordeide, Jarle T.; Folstad, Ivar (Frontiers in Ecology and Evolution, 2015)
How much of a fitness benefit is obtained by dominant males of external fertilizers from releasing ejaculates in synchrony with female egg-release when engaging in sperm competition, and what is the most important sperm trait for paternity in these situations? The Arctic charr (Salvelinus alpinus) is an external fertilizer experiencing intense male-male competition over reproductive opportunities including sperm competition. To compensate for their disadvantage the sneaker males, which often spawn out of synchrony with the female, produce more and faster sperm than the guarding males. We used controlled in vitro fertilization trials with experimentally produced dominant and subordinate, sneaker males to test what effect relative synchrony in gamete release, sperm quality (i.e., motility and velocity) and sperm quantity have on a male’s fertilization success in pair-wise sperm competitions. When the sneaker males released ejaculates after the guarding male there was no overall difference in fertilization success. The quality (i.e., motility and velocity) of a male’s sperm relative to that of the competing male was the best predictor of male fertilization success regardless of their mating tactic and spawning synchrony. The relative number of sperm cells also had an effect on fertilization success, but mainly when the dominant and sneaker male ejaculated synchronously. Our close imitation of natural sperm competition in charr shows that the sneaker males of external fertilizing species may fully compensate for their disadvantaged mating role by producing ejaculates of higher quality - an adjustment strangely not met by dominants.